EVALUATION OF SUCCESS OF RESIN INFILTRATION TECHNIQUE IN SUPERFICIAL PROXIMAL CARIOUS LESIONS OF POSTERIOR TEETH - Mahmood, Faisal; Munir, Muhammad Bader; Altaf, Ali; Yousaf, Ajmal; Bhangar, Faisal; Hussain, Syed Muzammil (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the effectiveness of resin infiltration technique in arresting superficial proximal carious lesions of posterior teeth. Study Design: Quasi experimental study. Place and Duration of Study: Operative dentistry department, de’ Montmorency College of Dentistry Lahore, from Oct 2018 to Mar 2019. Methodology: Meeting inclusion criteria were selected. Informed consent was obtained. After application of rubber dam; etchant gel was applied to superficial proximal carious lesions in these patients; water-rinsed and air-dried for 30 sec; resin was then infiltrated into each lesion. Patients were recalled after 6 months for follow up. Results: Total patients were 30 out of which 18 (60%) were males and 12 (40%) were females. Mean age of patients was 25.77 years ranging from 16-35 years. Success of resin infiltration technique in superficial proximal carious lesions in posterior teeth was 86.7% measured by bitewing radiograph taken on follow up after 6 months to see any progression of carious lesion. Conclusion: Resin infiltration was effective in 86.7% patients in arresting progress of superficial proximal carious lesions with no significant difference for age and gender. Hence it is suggested that resin infiltration being promising micro invasive approach should be considered in addition to non-operative and operative treatment approaches.